Development and diffusion of integrated Striga control practices for small-scale farmers in western Kenya - Friesen, Dennis K. (2001)
The parasitic weed Striga hermonthica has become one of the most significant constraints to cereal production in western Kenya. In 1995 a collaborative project was initiated to develop control technologies for Kenyan farmers.